Health Implications of Diverse Visions of Urban Spaces: Bridging the Formal-Informal Divide - Priya, Ritu; Singh, Ranvir; Das, Sayan (Frontiers in Public Health, 2019)
Abstract In the past 200 years, urban spaces have been imagined as neatly laid out, well-planned, sanitised and civilised places of dense human habitation with regulated economic activity, where political power, financial capital, the frontiers of knowledge and technology thrive. This has been the urban planners dream, even while it does not reflect the full reality, whether of cities in the LMICs or the HICs. In the face of such homogenising visions arising from Euro-American models, formal urban systems fail to provide adequately for residents’ needs, who then carve out their own resources and processes for meeting them, largely within the domain of urban ‘informality’. While large part of literature presents urban informality as reflected in the slum, others have shown how it is found in relation to all classes (1). The concept of informality has largely been applied to the core dimensions of economic life of the city. Applied to people’s ‘ways of life’, intermingling of the formal and informal becomes distinctly evident in everyday practices in locations such as the peri-urban, and in activities such as health care. This paper opens up the sphere of health care for urban planning that has, in recent decades, left it largely untouched. It uses data from a rapid assessment of health seeking behaviour of three socioeconomic groups—the middle class, slum-dwellers and homeless— in Delhi, the capital city of India. The findings, relevant beyond the specific location, reveal that people of all sections resort to myriad informal arrangements for their health care, challenging the dominant connotation of the formal-informal denoting a legitimate-illegitimate dichotomy. This provides potential directions to bridge the formal-informal divide, to re-configure urban planning towards more sustainable futures with plural visions of land use and urban greening for healthier urban conditions and for health care provisioning. The analysis posits that, besides the economic and political relations shaping the formal and informal, the politics of knowledge must be factored in if the informal has to be adequately understood for building sustainable futures.